2015
DOI: 10.1063/1.4918509
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of warpage induced by non-isothermal crystallization of co-polypropylene during the SLS process

Abstract: Abstract. Polymer processing using Additive Manufacturing Technologies (AM) has experienced a remarkable growth during the last years. The application range has been expanding rapidly, particularly driven by the so-called consumer 3D printing sector. However, for applications demanding higher requirements in terms of thermo-mechanical properties and dimensional accuracy the long established AM technologies such as Selective Laser Sintering (SLS) do not depict a comparable development. The higher process comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 13 publications
2
42
1
Order By: Relevance
“…Investigations on theoretical description of thermodynamic and kinetic process were started with modeling and simulation recently. 11 It could be shown that especially for PA12 powder, a model combining the Nakamura 12 with the Hoffmann-Lauritzen 13 theory, the determination of the crystallization rate presents a very good agreement with experimental results. Coupling the thermomechanical properties with the crystallization theory results in a better understanding of how the warpage or curling of parts develops during a SLS build in future.…”
Section: A Thermal Propertiesmentioning
confidence: 78%
“…Investigations on theoretical description of thermodynamic and kinetic process were started with modeling and simulation recently. 11 It could be shown that especially for PA12 powder, a model combining the Nakamura 12 with the Hoffmann-Lauritzen 13 theory, the determination of the crystallization rate presents a very good agreement with experimental results. Coupling the thermomechanical properties with the crystallization theory results in a better understanding of how the warpage or curling of parts develops during a SLS build in future.…”
Section: A Thermal Propertiesmentioning
confidence: 78%
“…The incidence of the laser beam just pushes the material over the melting point. Subsequently, the material remains in a molten, slightly undercooled state, where crystallization takes place only very slow [5]. The retarded crystallization ensures that dimensionally accurate parts can be fabricated.…”
Section: Introductionmentioning
confidence: 99%
“…To prevent shrinkage and deformations as an effect of rapid crystallization, the temperature of the built surface needs to be kept between the crystallization and melting temperature of the material [2][3][4]. The incidence of the laser beam just pushes the material over the melting point.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, equation (2) should be integrated in a global multiphysical integration scheme. For such applications, the reader may refer to references [16,17,19,20,21,22].…”
Section: Resultsmentioning
confidence: 99%
“…The Nakamura function G is plotted over [0,1] in Figure 1. This differential form, a first-order non-linear ordinary differential equation, is more natural to implement and solve numerically, especially in a multiphysical framework [16,17,18,19,20,21,22,23]. The initial state of the material (amorphous or semi-crystalline) should be given as an initial condition for α.…”
Section: Differential Formmentioning
confidence: 99%